Intravenous supplementation type and volume are associated with 1-year outcome and major complications in patients with chronic intestinal failure. Issue 10 (21st January 2020) - Pironi, Loris; Steiger, Ezra; Joly, Francisca; Wanten, Geert J A; Chambrier, Cecile; Aimasso, Umberto; Sasdelli, Anna Simona; Szczepanek, Kinga; Jukes, Amelia; Theilla, Miriam; Kunecki, Marek; Daniels, Joanne; et al.
Abstract : Background and aim: No marker to categorise the severity of chronic intestinal failure (CIF) has been developed. A 1-year international survey was carried out to investigate whether the European Society for Clinical Nutrition and Metabolism clinical classification of CIF, based on the type and volume of the intravenous supplementation (IVS), could be an indicator of CIF severity. Methods: At baseline, participating home parenteral nutrition (HPN) centres enrolled all adults with ongoing CIF due to non-malignant disease; demographic data, body mass index, CIF mechanism, underlying disease, HPN duration and IVS category were recorded for each patient. The type of IVS was classified as fluid and electrolyte alone (FE) or parenteral nutrition admixture (PN). The mean daily IVS volume, calculated on a weekly basis, was categorised as <1, 1–2, 2–3 and >3 L/day. The severity of CIF was determined by patient outcome (still on HPN, weaned from HPN, deceased) and the occurrence of major HPN/CIF-related complications: intestinal failure-associated liver disease (IFALD), catheter-related venous thrombosis and catheter-related bloodstream infection (CRBSI). Results: Fifty-one HPN centres included 2194 patients. The analysis showed that both IVS type and volume were independently associated with the odds of weaning from HPN (significantly higher for PN <1 L/day than for FE and all PN >1 L/day), patients' death (lower for FE, p=0.079), presence of IFALD cholestasis/liver failure and occurrence of CRBSI (significantly higher for PN 2–3 and PN >3 L/day). Conclusions: The type and volume of IVS required by patients with CIF could be indicators to categorise the severity of CIF in both clinical practice and research protocols.